Co-synthesis of ZnO / SnO2 mixed nanowires via a single-step carbothermal reduction method - Thanihaichelvan, T.; Haseeb, A.S.M.A.; Akbar, S.A.; Sabri, M.F.M. (Elsevier, 2013)
ZnO/SnO2 mixed nanowires are fabricated by a single-step in-situ carbothermal reduction of mixed ZnO and SnO2 powders with activated carbon under atmospheric pressure on a gold (Au) coated alumina substrate. Morphology and structural properties of the mixed nanowires are studied by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and transmission electron microscopy (TEM). FESEM investigation reveals the presence of uniform straight nanowires and branched hierarchical nanowires. The mixed nanowires have a diameter of about 15–80 nm and length ranging from two to several tens of micrometers, and thus having an aspect ratio above 1000. X-ray diffraction patterns show the crystalline nature of the ZnO/SnO2 mixed nanowires. Elemental mapping in a TEM suggests that the ZnO and SnO2 phases are mixed uniformly in the nanowire.
Keywords: Electron microscopy; ZnO/SnO2 mixed nanowire